Savannah Sparrows sent to J. Grinnell - DuMont, Philip A. (Philip Atkinson), 1903-1996 (2017)
Undated list of specimens. A list of Savannah Sparrow specimens sent to Joseph Grinnell in 1933 for identification, annotated with location and date of when it was collected, and the name of the collector.